Association Between Nutrition Knowledge and Maternal Nutritional Status Among Pregnant Women in Neglawangi Village, Bandung Regency, 2025: A Cross-Sectional Study - Ika Khairunnisa; Tri Arini Puspa Wati Manik; Filla Alfazriani Darson; Nely Bonita (Rifa'Institute, 2026)
Introduction: Maternal nutritional status during pregnancy is essential for maternal health and fetal growth; inadequate intake may lead to chronic energy deficiency and adverse outcomes. Objective: To determine the association between pregnant women’s nutrition knowledge and maternal nutritional status in Neglawangi Village, Kertasari District, Bandung Regency. Method: A quantitative cross-sectional study was conducted in August 2025 among all pregnant women in the village (total sampling; n = 35). Nutrition knowledge was measured using a structured questionnaire, and nutritional status was assessed using mid-upper arm circumference to classify chronic energy deficiency risk. Data were analyzed using univariate frequency distributions and a chi-square test at a 0.05 significance level. Result and Discussion: Most participants had a moderate level of knowledge (13/35; 37.1%), while more than half were classified as having chronic energy deficiency risk (18/35; 51.4%). Statistical testing showed a significant association between knowledge level and maternal nutritional status (p value = 0.016), indicating that knowledge is related to nutritional status in this setting. Conclusions: Pregnant women’s nutrition knowledge was significantly associated with maternal nutritional status, with a high proportion of chronic energy deficiency risk observed in the study population